Implementation Of Web Based Reservation System On Lembur Pancawati - Christianto, Yohanes; Marzuqi, Tubagus Ahmad; Sevani, Nina (Teknik dan Ilmu Komputer, 2017)
Website and the development of computer and internet, has big impact in the growth of hostelry business around the world including in Indonesia. Website can be used as a big data storage that efficient, effective, and persistent, which can be useful for hostelry management, like Lembur Pancawati. The use of website also simplify reservation staff at Lembur Pancawati to recording, saving, searching, and reporting guest data, better and faster, if compared with manual system. The use of reservation system based on website also helping the chair of Lembur Pancawati in monitoring and supervising guest data, through on time and detail report with minimal human error. YII framework is one of technology that can be used to make a website. The benefit of using YII framework is the availability of rules to speed up the process of websiteÃ¢â¬â¢s development. With many benefit, the use of reservation system based on website can help management of Lembur Pancawati to manage guest data, that at the end can improve services to guests. ÃÂ Keywords: web, reservation, framework